1988
DOI: 10.2307/2010315
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Political Explanations of Human Rights Violations

Abstract: G OVERNMENTS organize police forces and armies to protect their citizens, build schools and hospitals to educate and care for them, and provide financial assistance for the old and unemployed. But governments also kill, torture, and imprison their citizens. This dark side of government knows no geographic, economic, ideological, or political boundary. In the Middle East, for example, Iraq has morbidly placed a "welcome" doormat at the entrance to its torture chamber-a place where prisoners are burned with ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
216
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(226 citation statements)
references
References 5 publications
6
216
3
1
Order By: Relevance
“…Large scale cross-national comparative analyses that specify civil and political rights protection as the dependent variable tend to use a narrow and procedural definition of democracy as an independent variable (see, e.g. Landman, 2005aLandman, , 2005bLandman & Carvalho, 2016;Mitchell & McCormick, 1988;Poe & Tate, 1994) in an effort to minimise the problem of endogeneity. Such studies show that democracy and human rights are indeed positively correlated with one another but not perfectly so.…”
Section: Empirical Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large scale cross-national comparative analyses that specify civil and political rights protection as the dependent variable tend to use a narrow and procedural definition of democracy as an independent variable (see, e.g. Landman, 2005aLandman, , 2005bLandman & Carvalho, 2016;Mitchell & McCormick, 1988;Poe & Tate, 1994) in an effort to minimise the problem of endogeneity. Such studies show that democracy and human rights are indeed positively correlated with one another but not perfectly so.…”
Section: Empirical Relationshipsmentioning
confidence: 99%
“…Such studies show that democracy and human rights are indeed positively correlated with one another but not perfectly so. From the first cross-national study by Mitchell & McCormick (1988) to the latest pooled-cross section time-series models on human rights protection, there is a significant relationship between democracy and human rights.…”
Section: Empirical Relationshipsmentioning
confidence: 99%
“…that account for the variation in the protection of civil and political rights. 58 Subsequent studies use more complex data sets and additional domestic and international explanatory variables, which take into account such issues as direct foreign investment, structural adjustment loans, foreign aid, international treaty ratification, the presence of NGOs, membership of IGOs, globalisation and trade, among other factors. 59 In the case of inequality and human rights, the analysis found that even after controlling for other factors, there is indeed a significant relationship between high levels of income and land inequality on the one hand and the violation of physical integrity rights on the other.…”
Section: Going Globalmentioning
confidence: 99%
“…17 Section three uses the case of Brazil to show how insights from field observations can generate hypotheses that can be tested through large-N comparative analysis of the kind that has dominated much of empirical political science since 1980s. 18 Section four charts a course at the 'meso' level between single-country studies and large-N studies to illustrate the ways in which the comparative analysis of carefully chosen cases can take into account the contextual specificities of different countries, while yielding inferences about the protection of human rights that apply beyond the cases under consideration. The final section argues that the comparative analysis of human rights is grounded in a set of epistemological and philosophical assumptions that transcend the 'fact-value' dichotomies in the social sciences in ways that allow empirical methods to challenge the kind of power relations that makes the continued violation of human rights and human dignity possible.…”
mentioning
confidence: 99%
“…Comparative studies tend to emphasize two factors that are often associated with violations of personal integrity: economic development and democratic consolidation (Milner et al 1998;Mitchell and McCormick 1988). Quantitative studies of personal integrity violations provide a third relevant explanatory variable in the form of a measure for the frequency of these violations.…”
Section: Predicting Public Support For Torturementioning
confidence: 99%